China's spatial fix and 'debt diplomacy' in Africa: constraining belt or road to economic transformation?. Issue 1 (2nd January 2022) - Carmody, Pádraig; Taylor, Ian; Zajontz, Tim
ABSTRACT: Mounting overaccumulation of capital and material has compelled the Chinese government to seek solutions overseas. The Belt and Road Initiative (BRI), with its transregional infrastructure projects connecting Eurasia and Africa, is the hallmark venture in this effort. Chinese road, railway, port and energy projects, implemented under the BRI banner, have become widespread in Africa. This article traces drivers of the BRI in the post-reform evolution of the Chinese economy and conceptualises the BRI as a multi-vector "spatial fix" aimed at addressing chronic overaccumulation. Focusing on Kenya, Djibouti and Ethiopia, the paper documents how loan financing related to BRI projects reveals contradictions that arise from China's spatial fix in Africa. Concerns about a looming debt crisis on the continent and the questionable economic sustainability of some BRI projects have become more pressing amidst the COVID-19-induced economic contraction. Hopes for Africa's economic transformation based on increasing connectivity under the BRI are unlikely to materialise.